2016
DOI: 10.3390/ijms17050735
|View full text |Cite
|
Sign up to set email alerts
|

Sirolimus and Everolimus Pathway: Reviewing Candidate Genes Influencing Their Intracellular Effects

Abstract: Sirolimus (SRL) and everolimus (EVR) are mammalian targets of rapamycin inhibitors (mTOR-I) largely employed in renal transplantation and oncology as immunosuppressive/antiproliferative agents. SRL was the first mTOR-I produced by the bacterium Streptomyces hygroscopicus and approved for several medical purposes. EVR, derived from SRL, contains a 2-hydroxy-ethyl chain in the 40th position that makes the drug more hydrophilic than SRL and increases oral bioavailability. Their main mechanism of action is the inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 242 publications
(248 reference statements)
0
27
0
Order By: Relevance
“…The potential involvement of autophagy was then investigated, since RAD001 and mTOR inhibitors are described as autophagy activators (8,16), and also because the induction of apoptosis required a longer duration of RAD001 treatment. Autophagy and the autophagosome are controlled by specific interactions of several protein complexes: A protein complex including beclin-1 is required for phagophore nucleation, while another complex including the cytosolic and the lipidated form of LC3 protein (LC3I/LC3II) is necessary for elongation and closure of the autophagosome (17).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential involvement of autophagy was then investigated, since RAD001 and mTOR inhibitors are described as autophagy activators (8,16), and also because the induction of apoptosis required a longer duration of RAD001 treatment. Autophagy and the autophagosome are controlled by specific interactions of several protein complexes: A protein complex including beclin-1 is required for phagophore nucleation, while another complex including the cytosolic and the lipidated form of LC3 protein (LC3I/LC3II) is necessary for elongation and closure of the autophagosome (17).…”
Section: Resultsmentioning
confidence: 99%
“…Everolimus (RAD001) is derived from SRL and contains a 2-hydroxy-ethyl chain that makes the drug more hydrophilic than SRL, increasing its oral bioavailability by ~10-16% (7). The mechanism underlying the action of SRL and RAD001 is the inhibition of mTOR complex 1 and the regulation of factors involved in several cellular functions, including protein synthesis, regulation of angiogenesis, lipid biosynthesis, mitochondrial biogenesis and function, cell cycle and autophagy (8). RAD001 has received approval from the US Food and Drug Administration for the treatment of hormone receptor-positive advanced breast cancer in combination with exemestane in post-menopausal patients with non-steroidal aromatase inhibitor-refractory disease (9).…”
mentioning
confidence: 99%
“…Nevertheless, patients receiving targeted therapies often exhibit moderate or heavy toxicity likely attributable, as for chemotherapy, to the unselected target cells. In these patients, the mean short duration of the efficacy likely reflects the higher number of mechanisms potentially responsible for the development of resistance (Roskoski 2014, Fey et al 2016, Granata et al 2016. Recently, a plethora of these mechanisms of resistance has been investigated in melanoma skin cancer (Wellbrok & Arozarena 2016).…”
Section: Chemo Hormone and Targeted Therapies: Main Limitationsmentioning
confidence: 99%
“…They showed that CGTG-102 and DOX plus ifosfamide together are able to increase cell killing, as well as up-regulate ICD markers, such as secreted HMGB1 and ATP. Everolimus is a derivative of rapamycin and cellular inhibitor of mTOR, which has been approved for use in several renal and neurologic tumors [110]. Treatment of glioma tumors in vitro and in vivo with a combination of everolimus and the oncolytic Ad strain Ad-D24-RGD was shown to induce synergistic antitumoral activity [111].…”
Section: Inducing Icd In Combination With Other Drugsmentioning
confidence: 99%